A study on body mass index and its correlation with type 2 diabetes - Jain, Subhash Chand; Gupta, Rameshwar Prasad; Gupta, Deepak; Jain, Madhu Kanta (International Journal of Research in Medical Sciences, 2017)
Obesity and increases in body weight are among the most important risk factors for type 2 diabetes mellitus. Obesity contributes to the development of type 2 diabetes mellitus. Body mass index is also known as obesity index. Body mass index is a strong and independent risk factor for being diagnosed in cases of type 2 diabetes mellitus. There is a high risk of type 2 diabetes in those who have a higher body mass index. The present study has been done with the objective of finding correlation between BMI and type 2 diabetes.